Role of Model GST Law on Automobile Sector: Examining the Impact of Model GST Law on the Indian Automotive Industry (Journal of Advances and Scholarly Researches in Allied Education, 2021)
After the 1990s, India's economic reforms propelled the country's emergence as a globallyconnected nation, with notable gains in regulatory effectiveness, macroeconomic stability, andgeopolitical steadiness. One of the fastest-growing economies on the Asian continent has been India inrecent years. With the introduction of GST, India's indirect tax system stands to undergo a significantshift. As a result, it's sometimes referred to as the mother of indirect taxes since it will include the vastmajority of the other types, making it easier for taxpayers to understand. The article explains the historyand purpose of the planned GST and its impact on the Indian economy, with a focus on the automotiveindustry. The relevance of GST is re-examined in the study, and the conclusion is drawn.